Product Development and Innovation using Alternative Material - Fadli, Izzil; Fatchurrohman, Nanang (Universitas Putra Indonesia YPTK Padang, 2024)
Rattan as an alternative material in product, has a significant resource for personal use and commercial activities in Indonesia, particularly in West Sumatra. Initially, its trade focused on raw materials and semi-finished products, but it later evolved into the production and distribution of finished rattan goods, managed primarily by wholesalers in the region. Beyond rattan processing, finished rattan products have been extensively marketed. In recent years, rattan's application has expanded into the realm of interior design, finding use in furniture and interior accessories. Alongside natural rattan, synthetic rattan has emerged as an alternative material, created using synthetic base materials to serve as substitutes. This innovation originated from efforts by the government and artisans to address material shortages while promoting environmental sustainability. Synthetic rattan offers versatility in texture, color, and shape, making it easy to combine with other materials such as aluminum and iron. Despite the traditional perception of rattan furniture, particularly chairs, as outdated, synthetic rattan furniture has gained popularity due to its adaptability to modern design trends. Craftsmen have developed synthetic rattan chairs in various styles, catering to evolving tastes and preferences. These products are increasingly utilized to meet the high demand for diverse designs in the interior design industry. To better understand this growing trend, qualitative research has been conducted to explore the expanding role of rattan—both natural and synthetic—in interior design and its implications for production and trade.